Demonstrative motivation - Viliūnas, Vytis; Kravčenko, Anna (Psichologija, 2001)
Investigations of human social behavior (self-presentation, self-strenghtening) confirm the conclusion in the authors' previous article about evolutionary autonomisation of demonstrative behavior, its emancipation from phylogenetically primary motivation. They show universal and flexible usage of demonstrative behavior for satisfaction of various human needs. Some theoretical problems, important for general concept of motivation are specifically elucidated by such broad manifestation of demonstration. It is in line with and illustrates the statement about unavoidable polymo-tivation of human behavior; contradicts widespread tendency to treat motivation as a set of discrete phenomena (motives, drives, dispositions etc.), which arouse behavior separately; and confirm alternative integrative interpretation of motivation, by which all its components express themselves together and interact with each other. The variety of demonstrative motivations is described by choosing five cases of its generalized forms of goal orientation. They are: 1) autonomic self-demonstration, usually manifesting itself in otherwise motivated behavior as a person preoccupation by impression he is making on others; 2) instrumental acquisitive demonstration used for achievement of positive aims and 3) instrumental defensive - for avoiding undesirable consequences; 4) demonstration, which saves or changes self-image by assimilation of opinion about oneself produced on others and 5) demonstration used for the relaxation of tension.Data considered in articles indicates that demonstrative motivation is basic, i.e. influencing, sometimes markedly, the development of other human motivation. It has phylogenetical roots, develops in ontogenesis and is not pathological, although sometimes has too excessive manifestation.
Keywords: demontrative; motivation